Illustrations and Studies in Neotropical Orchidaceae. 3. On the identity of Dracontia pachyglossa and D. ramonensis; with a new species, D. lueriana (Pleurothallidinae) - Karremans Lok, Adam Philip (2012)
The Costa Rican Dracontia ramonensis is discussed and illustrated. It had been already illustrated as early as 1867 by A.R. Endres, but only described in 1923 by Rudolf Schlechter. Costa Rican specimens of that species have been misidentified as Dracontia pachyglossa, a species known only from Mexico and Guatemala. Additionally the name Dracontia ramonensis has been incorrectly applied to an unnamed species from Costa Rica, here described and illustrated as D. lueriana.